Penggunaan material berubah fasa sebagai penyimpan energi termal pada bangunan gedung - Hamdani Umar (Jurnal POLIMESIN, 2020)
The energy consumption of the world building sector reaches 30% of overall energy consumption and accounts for one third of greenhouse gas emissions worldwide. Thermal energy storage is a simple and effective technique to be applied to buildings to improve building energy efficiency, and is expected to reduce the environmental impacts associated with energy use. Thermal storage by utilizing phase change material (PCM) is the most promising technique because of its high energy storage capability and small temperature changes. The combination of building materials and PCM is an efficient way to increase the thermal energy storage capacity of building components for the purpose of storing thermal energy directly in buildings. In this study the results of testing the use of beeswax as a phase change material in building concrete are given. The test results of concrete equipped with beeswax as PCM decreased the strength of the concrete but on the other hand it was able to absorb and store heat energy. The results of application analysis in buildings are able to reduce indoor cooling loads.